Streambank erodibility and lateral instability hazard in the Manahara River, Kathmandu basin, Nepal - Shrestha, Pramila; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2007)
The Manahara River, a large tributary of the Bagmati River, is located in the northeast of the Kathmandu basin. Recently, the river (especially, its lower reach) has been excessively mined for sand and gravel. Such anthropogenic activities together with the natural processes have led to rapid and haphazard shifting of its channel. As a result, its banks and adjacent areas are subject to failures and other mass movements. In this paper, the river course is evaluated in terms of its bank erosion and lateral instability (BELI) hazard by considering bank erodibility hazard index, near-bank stress index, lateral instability hazard index, and anthropogenic disturbances. The downstream reaches of the fourth-order stream belong to a moderate BELI hazard, whereas the fifth-order stream in the middle reach, near Mulpani, falls under a very high hazard. The rest of its fifth-order stretch exhibits a high hazard. An increase in the degree of anthropogenic disturbances increases the BELI hazard in the downstream stretch of the river. Poor riparian vegetation seems to be one of the factors aggravating the bank erodibility hazard in the river. Hence, the restoration of bank vegetation and establishment of riparian vegetation buffer zones can significantly reduce the BELI hazard.